BEHAVIORAL THEORY VIEWED FROM THE PERSPECTIVE OF CONSUMER BEHAVIOR TO BE APPLIED TO PRODUCER BEHAVIOR - Farida Yani; Rahmat Syahni; Rika Ampuh Hadiguna; Novizar Nazir (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Human behavior is one of the fields of study that is very interesting to study that has no end. Because humans are actors of all life activities. All lines of life are controlled through human behavior both as individuals and groups. The author uses a systematic literature review method. Articles obtained through the search media Google Scholar, Sciencedirect, Researchgate, Elsevier, and Schimago. The keywords used in the search are behavior, consumer behavior, behavior form, consumer, and producer. This research is to analyze behavioral theory viewed from the perspective of consumer behavior to be applied to producer behavior. The results showed that many social analysts do not believe that instinct is the source of social behavior. For example, William James, a psychologist, believes that although instincts are the things that influence social behavior, the main explanation tends to be habits, namely behavioral patterns that are acquired through repetition throughout a person's life. Here the author presents several behavioral theories based on the results of previous literature studies by considering articles that are still relevant in this literature review, among them Mc Dougall theory, Push Theory, Attribution Theory, Cognitive Theory, Theory